Why Nigeria abstains from borrowing in the Euro-market. - Falegan, S. B.; Central Bank of Nigeria (CBN). (Lagos: Central Bank of Nigeria (CBN), 1977)
This is a paper presented by S. B. Falegan, Director of Research, Central bank of Nigeria at the meeting of Group of Experts on "Alternative Solutions to the External Public Debt Problems of the LDCs" at the EL Colegio de Mexico, Mexico from 26-30 October 1977.
lje 7/3/19
Arch
Keywords: External debt; Public debt; Nigeria